ASPECTS REGARDING THE REGULATION AND APPLICATION OF LOCAL AUTONOMY IN ROMANIA - PART II - MELINDA CENUŞE (Annals of the University of Petrosani: Economics)
The second part of this study continues to analyze local autonomy, as the fundamental principle of the administrative-territorial organization, in the light of the Romanian Administrative Code. Romanian administrative law has waited for almost 30 years the codification of major administrative law institutions and finally in 2019 the long-awaited Code has appeared. According to the Administrative Code, local autonomy is exercised by local public administration authorities and it is only administrative and financial, being exercised on the basis and within the limits provided by law. Local autonomy concerns the organization, functioning, competence and duties of local public administration authorities, as well as the management of resources that, according to the law, belong to the township, city, municipality or county, as the case may be. Local autonomy guarantees local public administration authorities the right, within the limits of the law, to take initiatives in all fields, except for those expressly given in the competence of other public authorities.